Development of European electoral and referendum law - Kaminska, Nataliia (ScienceRise: Juridical Science, 2022)
The purpose of the article is to study European electoral and referendum law. In order to achieve it, it is necessary to solve the following tasks: disclosure of the nature of European electoral and referendum law; analysis of existing European legal standards in this field; highlighting the trends and regularities of the development of European electoral and referendum law in modern conditions. The methodological basis of the research is general scientific methods, in particular, dialectical, systemic, synthesis method, etc., and special legal (comparative-legal, historical-legal, formal-logical, structural-functional, legal semiotics, etc. .) methods of scientific knowledge. Their combination made it possible to comprehensively analyze the essence and peculiarities of European electoral and referendum law, to find out the trends and prospects of their development in modern conditions. With the creation of an extensive system of international legal standards of the universal and regional (mostly European) levels, which guarantee the rights of citizens to participate in elections and referendums, the active functioning of the Council of Europe, the OSCE, the EU, the traditional democratic institutions of elections and referendums are marked by significant modernization and standardization. Along with the development of electoral and referendum law and relevant legislation at the domestic levels, the formation of European electoral and referendum law is observed. Undoubtedly, thorough studies of their nature and essence, subject-functional and other characteristics, mechanisms of implementation of existing European legal standards in this field, etc., are necessary. The risks and threats, associated with armed aggression against Ukraine, and the re-creation of classic institutions of people's power, for the improvement of which the efforts of democratic states and, in recent decades, international organizations have been concentrated, force the development of effective tools for countering and preventing manipulation of elections and referenda, establishing responsibility for such acts, increasing universally binding (normative) acts, along with "soft law" acts in this area